The first state of the Russion Revolution : lost texts of critical marxism, volume 1 - Matgamna, Sean; Trotski, Leon; Shachtman, Max; Draper, Hal; Burnham, James (London: Phoenix Press, 1998)
"Edited by Sean Matgamna ; articles by Max Schachtman, Hal Draper, C.L.R. James, Al Glotzer, Joseph Carter, Leon Trotsky, James Burnham and others"